Association of subclinical carotid atherosclerosis with immediate memory and other cognitive functions. Issue 1 (4th August 2017) - Matsumoto, Lumine; Suzuki, Kazushi; Mizuno, Yoshiko; Ohike, Yumiko; Ozeki, Atsuko; Ono, Satoshi; Takanashi, Mikio; Sawaki, Daigo; Suzuki, Toru; Yamazaki, Tsutomu; Tsuji, Shoji; Iwata, Atsushi
Abstract: Aim: To clarify whether carotid atherosclerosis and its risk factors are associated with cognitive decline. Methods: We evaluated 206 individuals who visited our center for health screening. We carried out physical examinations, blood tests, intima‐media thickness (IMT) measurement by carotid ultrasonography, brain magnetic resonance imaging scanning and cognitive function assessments. A total of 30 individuals, who had significant cerebrovascular lesions detected in magnetic resonance imaging scans, were excluded. To detect early cognitive decline, we defined "cognitive impairment (CI)" when a patient satisfied at least one of three criteria. These were Mini‐Mental State Examination score <24, clock‐drawing test score <4 coexisting with forgetfulness and Wechsler Memory Scale‐revised delayed recall score below the normal range for the duration of education (>16 years of education: ≥9, 10–15 years: ≥5, 0–9 years: ≥3). Results: Among 176 individuals, 27 were placed in the CI group. IMT was significantly higher in the CI group as compared with the non‐CI group (mean ± SD: 2.0 ± 1.0 vs 1.7 ± 0.7, P = 0018 by Student's t ‐test). Other atherosclerotic risk factors, such as blood pressure, low‐density lipoprotein cholesterol, and hemoglobin A1c, were not significantly different between the two groups. In multivariate analysis, maximum IMT was associated with impaired immediate recall score on Wechsler Memory Scale‐revised, independent of the presence of deep white matter hyperintensities on the magnetic resonance imaging scan. Conclusions: Subclinical carotid atherosclerosis, defined as thickened IMT, could be a marker for early stages of CI, especially for immediate memory recall. The impairment is presumably caused by inducing cerebral microvascular dysfunction in the frontal lobe.Geriatr Gerontol Int 2018; 18: 65–71 .